A Dosimetric Comparison of Dose Escalation with Simultaneous Integrated Boost for Locally Advanced Non-Small-Cell Lung Cancer. (28th May 2017) - Yang, Wenjuan; Zeng, Biao; Qiu, Yanfang; Tan, Jianfeng; Xu, Shilei; Cai, Yilong; Zhou, Yujuan; Liu, Zhigang; Luo, Junming; Wang, Hui
Abstract : Background . Many studies have demonstrated that a higher radiotherapy dose is associated with improved outcomes in non-small-cell lung cancer (NSCLC). We performed a dosimetric planning study to assess the dosimetric feasibility of intensity-modulated radiation therapy (IMRT) with a simultaneous integrated boost (SIB) in locally advanced NSCLC. Methods . We enrolled twenty patients. Five different dose plans were generated for each patient. All plans were prescribed a dose of 60 Gy to the planning tumor volume (PTV). In the three SIB groups, the prescribed dose was 69 Gy, 75 Gy, and 81 Gy in 30 fractions to the internal gross tumor volume (iGTV). Results . The SIB-IMRT plans were associated with a significant increase in the iGTV dose ( P < 0.05), without increased normal tissue exposure or prolonged overall treatment time. Significant differences were not observed in the dose to the normal lung in terms of the V5 and V20 among the four IMRT plans. The maximum dose (Dmax) in the esophagus moderately increased along with the prescribed dose ( P < 0.05). Conclusions . Our results indicated that escalating the dose by SIB-IMRT is dosimetrically feasible; however, systematic evaluations via clinical trials are still warranted. We have designed a further clinical study (which is registered with ClinicalTrials.gov, number NCT02841228 ).